(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2023)
Gender equality is clearly framed by and defined in the knowledge society in particular. Struggles towards all goals in this regard unfold in the context of a large gender gap and unequal distribution of power. These are circumstances in which women are clearly disadvantaged, facing obstacles in every aspect of their lives: family, relationships, education, and, therefore, work. Occupying senior leadership roles in institutions related to science and research remains an arduous task. The study takes a descriptive and analytical approach, drawing on official documents by international agencies such as UN, UNESCO, UN WOMEN, ECLAC, WB, IDB, and CODS as well as specialist websites. Title searches were carried out and variables identified through key words and phrases in recently published scientific articles found in open-access databases and scientific journals such as Scopus, WOS, SciELO, Redalyc. It found that intensive assertion of claims has resulted in the enshrinement of many women’s rights, the unconditional support of an array of international organizations, advances in narrowing the gender gap, and the positioning and leadership of women in professional scientific contexts, as part of the broader pursuit of parity between men and women.